Student’s ways of thinking and ways of understanding analysis in solving mathematics problems in term of adversity quotient - Lailiyah, Siti; Fitria Anis Kurlillah; Kusaeri (Universitas Islam Negeri (UIN) Mataram, 2023)
[English]: There are two categories of thinking skills that influence each other in mathematical knowledge, namely a thinking process called ways of thinking (WoT) and ways of understanding (WoU). This study aims to describe students' WoT and WoU in solving mathematics problems in terms of adversity quotient (AQ). This research is descriptive and qualitative. The participants of this study were students at MTs Muhammadiyah 1 Taman Sidoarjo. The subjects were selected based on the results of the adversity response profile test using a purposive sampling technique, so there were 3 climbers, 3 campers, and 2 quitter. The written test and interview data were analyzed according to the WoT and WoU indicators. The results of this study indicate that the WoT climber students tend to have one strategy in solving mathematical problems that leads to the correct solution, an empirical WoT, and a very good belief in mathematical concepts. Meanwhile, the WoT campers and quitters tend to have one strategy that leads to wrong solutions, and beyond belief WoT. The camper students have good confidence, while quitter students have less confidence in mathematical concepts. The WoU climber students are in the very good category, camper students are enough, and quitter students are in the less category. The WoT and WoU of climber students are better than those of camper and quitter students. [Bahasa]: Terdapat dua kategori keterampilan berpikir yang saling mempengaruhi dalam pengetahuan matematika yaitu proses berpikir yang disebut ways of thinking (WoT), dan cara pemahaman siswa yang disebut dengan ways of understanding (WoU). Penelitian ini bertujuan untuk mendeskripsikan WoT dan WoU siswa dalam menyelesaikan masalah matematika ditinjau dari adversity quotient (AQ). Penelitian ini adalah deskriptif kualitatif. Partisipan dalam penelitian ini merupakan siswa di MTs Muhammadiyah 1 Taman Sidoarjo. Subjek dipilih berdasarkan hasil tes adversity respons profile menggunakan teknik purposive sampling, sehingga didapatkan 3 siswa climbers, 3 campers dan 2 quitters. Data tes tulis dan wawancara dianalisis sesuai indikator WoT dan WoU. Hasil penelitian ini menunjukkan bahwa WoT siswa climber dalam menyelesaikan masalah matematika cenderung memiliki satu strategi yang mengarah pada solusi benar, cara berpikir empiris, dan memiliki keyakinan yang sangat baik terhadap konsep matematika. Sedangkan WoT siswa camper dan quitter cenderung memiliki satu strategi yang mengarah pada solusi salah, dan cara berpikir luar keyakinan. Siswa camper memiliki keyakinan yang baik, sedangkan siswa quitter memiliki keyakinan yang kurang terhadap konsep matematika. WoU siswa climber berkategori sangat baik, siswa camper berkategori cukup. dan siswa quitter berkategori kurang. WoT dan WoU siswa climber lebih baik dibandingkan siswa camper dan quitter.